Grammatical Interference in the Aceh Language in the Use of Indonesian Writing Variety of 7th Grade Students of Junior High School 1 Indrapuri Aceh Besar District and Their Utilization as Teaching Materials in Learning to Write Narrative Texts - Jannati Wardah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to describe: (1) forms of basic word interference and derivatives of Acehnese language in Indonesian narrative essays, (2) forms of Acehnese sentence pattern interference in narrative essays, (3) their use as teaching language in learning to write narrative texts. The method used in this research is descriptive qualitative method. The subjects of this study were students of class VII-A and students of class VII-Byang totaling 65 people. The results showed there were grammatical interference and their use as teaching materials in learning to write narrative texts. As for the morphological interference form in the base word there are 15 data and in the word derivative (affixation) there are 37 data consisting of: prefix (prefix) meu- 6 data, data peu- 2, data te-6, data si-5, and financial - 1 data. Inserts (infix) consist of -eun- 2 data, -eum- 3 data and -eul- 1 data. The suffix consists of –an 2 data, and -kon 2 data. The prefix and suffix consist of data 2 and data 2 data. While for the form of repetition (reduplication) there are 3 data. Form of interference at the level of syntax (sentence patterns) there are 9 data consisting of S-P 3 data, S-P-O 1 data, S-P-Pel 1 data, S-P-O-Pel 1 data, S-P-O-K 1 data, and S-P-K 2 data. For its use as teaching material in learning to write narrative text, the writer makes a hand out.